2015
DOI: 10.1534/genetics.115.178483
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genes Involved in Controlling Specification of Drosophila FMRFamide Neuropeptide Cells

Abstract: The expression of neuropeptides is often extremely restricted in the nervous system, making them powerful markers for addressing cell specification . In the developing Drosophila ventral nerve cord, only six cells, the Ap4 neurons, of some 10,000 neurons, express the neuropeptide FMRFamide (FMRFa). Each Ap4/FMRFa neuron is the last-born cell generated by an identifiable and wellstudied progenitor cell, neuroblast 5-6 (NB5-6T). The restricted expression of FMRFa and the wealth of information regarding its gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 83 publications
1
52
0
Order By: Relevance
“…Kip1 /p57 Kip2 or Cdkn1a/ b/c) (Baumgardt et al, 2014;Bivik et al, 2015). In addition, several late-acting cues were identified that control the type I>0 switch, including the late temporal genes castor (cas) and grainy head (grh), as well as the Hox gene Antennapedia (Antp).…”
Section: /P27mentioning
confidence: 99%
See 2 more Smart Citations
“…Kip1 /p57 Kip2 or Cdkn1a/ b/c) (Baumgardt et al, 2014;Bivik et al, 2015). In addition, several late-acting cues were identified that control the type I>0 switch, including the late temporal genes castor (cas) and grainy head (grh), as well as the Hox gene Antennapedia (Antp).…”
Section: /P27mentioning
confidence: 99%
“…These regulators exert their roles by regulating the key cell cycle genes (Baumgardt et al, 2014). In addition, the canonical Notch pathway was also found to be important for the type I>0 switch, via regulation of all four key cell cycle genes (Ulvklo et al, 2012;Bivik et al, 2015Bivik et al, , 2016. Notch signaling is initially off in NBs -a prerequisite for establishment of NB cell identity in the neuroectoderm -but is gradually activated during lineage progression (Ulvklo et al, 2012;Bivik et al, 2016).…”
Section: /P27mentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggested critical roles for the Snail family, particularly wor, within the NBs [276]. In addition, wor was identified in our genetic screen that suggests it to be critical for lineage progression and driving NBs in type I division mode [217].…”
Section: Worniu (Wor)mentioning
confidence: 84%
“…After testing a large number of transgenic lines, two Ap4/FMRFa-eGFP transgenic lines were identified, one on second and one on third chromosomes, that allowed for detecting eGFP expression in the Ap4 neurons of the living embryos and larvae under the fluorescent microscope. [217].…”
Section: Nb5-6t Lineage As a Modelmentioning
confidence: 99%